2014
DOI: 10.1515/eujal-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Creating rich language environments for more than one language: A work in progress in Flemish childcare

Abstract: This paper discusses language policy and practices in early educational settings in Flanders (Belgium). It describes the Flemish context and the challenges ECEC face. Stakeholders' beliefs and observed linguistic practices in ECEC in general and in the province of Flemish-Brabant are presented based on a small scale quantitative and qualitative study. We also discuss how major stakeholders have shaped language policy concerning language stimulation and multilingualism in recent years and how a new policy is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…In Denmark the nonindigenous population is very diverse, with the largest share of immigrant children coming from Turkey, Lebanon, Pakistan, Iraq, and Somalia (Danmarks Statistik, 2014). A study in Flanders, Belgium, which has similar heterogeneous groups in ECE, revealed that teachers feel ill prepared to deal with immigrant children and their families, mostly because of language difficulties and differing cultural values (Michel & Kuiken, 2014;Van Gorp & Moons, 2014). Recently, Europe has had to deal with increasing immigration of refugees mainly from Syria and Afghanistan (Ministry of Immigration, Integration and Housing, 2016), of which Denmark had an above-average number, which poses even more challenges for professionals working with children and their families.…”
Section: Implications and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In Denmark the nonindigenous population is very diverse, with the largest share of immigrant children coming from Turkey, Lebanon, Pakistan, Iraq, and Somalia (Danmarks Statistik, 2014). A study in Flanders, Belgium, which has similar heterogeneous groups in ECE, revealed that teachers feel ill prepared to deal with immigrant children and their families, mostly because of language difficulties and differing cultural values (Michel & Kuiken, 2014;Van Gorp & Moons, 2014). Recently, Europe has had to deal with increasing immigration of refugees mainly from Syria and Afghanistan (Ministry of Immigration, Integration and Housing, 2016), of which Denmark had an above-average number, which poses even more challenges for professionals working with children and their families.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Therefore, it seems timely to better prepare teachers in how to support this new group of children entering preschools and their families. One way could be through professional development, which can be an effective means of enhancing cultural awareness and supporting multilingualism (e.g., Michel & Kuiken, 2014;van Gorp & Moons, 2014).…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Most decision makers in Flemish education favor immersion in Dutch as a way of minimizing the presumed negative effects of the lack of Dutch use in immigrant-background families on L2 acquisition and school outcomes. A monolingual ideology prevailing in Flemish education and society underpins the central policy line of maximally expanding exposure to Dutch (Agirdag, 2010;Pulinx et al, 2017;Van Gorp & Moons, 2014). The present study was conducted in the midsize city of Ghent, which over the past six decades has gone through consecutive immigration influxes and is marked by growing levels of ethnolinguistic diversity.…”
Section: Study Settingmentioning
confidence: 99%
“…It has been suggested that professionals working in these educational settings should acknowledge the diversity in (pre)schools rather than ignoring it, and be responsive to the needs of the culturally diverse group of parents. Moreover, it implies that the teachers should acquire or strengthen their intercultural competences in order to cope with the diversity of parents and children (Van Gorp & Moons, 2014;Michel & Kuiken, 2014;OECD, 2013;Romijn et al, 2020;Young, 2014).…”
Section: Challenges For Establishing and Improving Educational Partnershipsmentioning
confidence: 99%